STUDY OF RISK FACTORS, CHEST X-RAY FINDINGS, AETIOLOGICAL AGENTS AND THEIR SENSITIVITY PATTERN AMONG PATIENTS WITH LOWER RESPIRATORY TRACT INFECTION - SHARADADEVI MANNUR,; ARCHANA BR,; SHUBHAKARA K,; NAGARAJ ER, (International Journal of Pharma and Bio Sciences, 2015)
Respiratory tract infections are the most common infectious disease in humans. It is the leading cause of mortality and morbidity in critically ill patients in developing countries.The aim of the present study was to evaluate the risk factors, chest x ray findings, aetiological agents and their antimicrobial susceptibility pattern in hospitalized patients with lower respiratory tract infection. A total of 200 sputum samples collected and processed. Organisms were identified and antimicrobial susceptibility of bacterial isolates was performed using standard procedures. Of the 200 samples 87 yielded growth. Pseudomonas aeruginosa was the predominant isolate followed by Klebsiella pneumoniae, Staphylococcus aureus. Antibiotic susceptibility pattern showed that carbapenem, aminoglycosides and fluroquinolones are most effective against Gram negative bacteria. Glycopeptide,macrolides and fluroquinolones effective against Gram positive bacteria. Hence regular monitoring of the changing trends of prevalent strains and their antimicrobial susceptibility patterns is required for the good management of patients.